Listen to the science! Which science? Regenerative research for times of planetary crises - Raffoul, Alexandre Wadih (Frontiers in Sustainability, 2023)
In situations where scientists disagree, which science should decision-makers listen to? This article argues that we should listen to “regenerative research,” that is, research (1) whose objective is to regenerate our relationship to the land and to each other (rather than dominating nature), (2) whose worldview acknowledges the interconnection between humans and non-humans (rather than assuming a separation between humanity and nature), and (3) whose processes are democratized (instead of including but a narrow circle of researchers). We should listen to regenerative science not because it is suited to the interests of politicians or activists, but because it is most likely to be beneficent, rigorous, and objective. In addition to granting scientists new responsibilities, such as engaging in public action, the climate and ecological crises therefore also require us to critically reflect on the core of our work: the knowledge we generate.